COMPARATIVE EVALUATION OF AN IN-HOUSE AND OMMERCIALLY AVAILABLE MEDIUM FOR DETECTING CARBAPENEM RESISTANT GRAM NEGATIVE BACILLI IN SURVEILLANCE RECTAL SWAB AND DENTIFICATION OF PREDISPOSING RISK FACTORS FOR OLONIZATION - POOJA G. SHAH; ANUSHA B.; SWETA R. SHAH; S. D. KAMAT; D. V. KAMAT (International Journal of Pharma and Bio Sciences, 2015)
Carbapenem resistant Gram negative bacilli (CR-GNB) are an increasing problem worldwide, and rectal swab surveillance is recommended as a component of infection control programs. The performance of an in-house medium (modified CDC protocol) for detecting CR-GNB in surveillance rectal swab was evaluated and compared with a chromogenic medium (ChromID CARBA). 40 rectal swab specimens were taken from different patients hospitalized in ICU and screened. Identification of isolates was done using standard biochemical tests and sensitivity using Kirby Baur disk diffusion method. Sensitivity (95.83%) and PPV (92 vs. 88.46%) of the in-house and CARBA agar were comparable whereas specificity of in-house medium was slightly higher than CARBA agar (88.89 vs. 83.33%). Colonization with CR-GNB was independently associated with exposure to carbapenem (p = 0.015). In conclusion, in-house medium as per CDC protocol (modified) has the potential to provide useful tool for convenient and inexpensive screening method for CR-GNB surveillance.